MORE RICE...IF FEWER RESTRICTIONS - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
To reduce imports, ACP countrios launched large irrigated rice programmes. Through heavy investments and high recurrent costs, they hoped to make irrigated rice cultivation the symbol of a new type of agricultural development This intensive...